The Diversity of Echinoderms in Intertidal Zone of Sundak Beach, Gunung Kidul, Yogyakarta, Indonesia - Herin Yoga Lesti; Syifa Evilia Maharani; Naila Nabila Rahmani; Fania Baeta Roska Khalallia; Ni Made Sri Winasti; Achmad Mustofa Huda; Septi Lutfiatun Nafiah; Rury Eprilurahman (BiosciED: Journal of Biological Science and Education, 2021)
Indonesia is a maritime country with high diversity of marine biota, which one is from Phylum Echinoderms. Echinoderms are known as biota of marine which is are living on corals, sandy, and on the intertidal zone and deep ocean. The intertidal characteristics of Sundak Beach has a suitable structure to echinodems life because there are many corals, but there is many species has not been identified before. The purpose of this research is to know the diversity of echinoderms phylum on the intertidal zone. Sampling was carried out on August, 24th 2019 with purposive random sampling method along the coastal-line in intertidal zone. The result of this research are identified and classified on the each class. Based on the results, the are found species from Echinodea, Holothuroidea, and Ophiuroidea. Species from Echinoidea are Tripneustes gratilla, Echinometra mathaei, Heterocentrotus trigonarius, Diadema antillarum., and Echinothrix calamaris. Holothuroidea namely Holothuria atra. Ophiuroidea namely Ophiotrix fragilis, Ophiocoma scolopendrina, and Ophiocoma erinaceus. The conclusion from this study is the discovery of five species from class Echinoidea, one species from class Holothuroidea and three species from class Ophiuroidea.